The Effect of Pair Check Learning on The Learning Outcomes of Grade X Students of State Vocational School 1 Panai Hulu - Layla Fitri; Eka Susanti (Journal of General Education and Humanities, 2025)
Students' academic performance at SMK N 1 Panai Hulu has not consistently met the expected minimum standards. A major contributing factor is the limited variety of teaching methods teachers use, which has resulted in low student engagement and passive learning. While previous studies have shown that cooperative learning models can improve student outcomes, many have not specifically examined their application in history learning within vocational school contexts. This study addresses that gap by applying the Pair Check learning model, which encourages students to take a more active role through independent and collaborative learning. A quantitative approach with a quasi-experimental design was employed. The population consisted of all tenth-grade students, and a sample of 70 students was selected, comprising 35 in Class A and 35 in Class B. Data were collected through pretests and posttests administered before and after the intervention, then analyzed using SPSS version 26. The results revealed a clear improvement in the experimental group: the average score increased from 69.71 (pretest) to 78.03 (posttest), surpassing the school’s minimum criteria. In comparison, the control group improved only from 69.34 to 72.29. An independent samples t-test confirmed this difference was statistically significant (sig. 2-tailed = 0.000 < 0.05). These findings demonstrate that the Pair Check model positively impacts student achievement in history learning. Beyond this context, Pair Check can be integrated into other subjects to foster active participation, peer accountability, and deeper understanding, offering teachers a practical alternative to conventional, teacher-centered methods.